The impact of the Covid-19 pandemic on a reference oral medicine service in Brazil - Marques, Esther Ferreira; Sousa, Viviane Nascimento; Campos, Eduardo Henrique; Ito, Fabio Augusto; Pires, Willian Ricardo; Tanaka, Jefferson Luís Oshiro (Journal of Oral Diagnosis, 2023)
The COVID-19 pandemic in 2020 had a global impact on healthcare services, leading to a decrease and delay in diagnosing various diseases and initiating treatment. Dentistry was quickly recognized as a high-risk area for contamination, resulting in a reduction in the number of consultations conducted. The objective of this study was to identify the main characteristics of consultations at the Oral Medicine Outpatient Clinic from our institution, comparing the number of consultations and diagnoses performed during regular years from 2016 to 2019 with the years of the COVID-19 pandemic. Materials and Methods: Data were collected and analyzed from clinical records of all patients seen at the Oral Medicine Outpatient Clinic from March 2016 to May 2021. Sociodemographic data and the diagnosis stablished for these patients were collected. In the pre-pandemic period, an average of 324 patients per year were treated. In the pandemic period average was 248.5 per year, indicating a 23.3% reduction in the number of patients treated at the service. When comparing the number and overall percentage of diagnosis stablished, a higher number of malignant neoplasms were identified during the pandemic, despite the reduction in services provided. Thus, we conclude that the COVID-19 pandemic had a negative impact on the total number of new patients admitted to our service but we were able to continue diagnosing cases of malignant neoplasms. This reinforces the importance of maintaining the service, considered essential to the population, during this critical period we have gone through.